Substantial role of under‐ice limnological processes in diatom dynamics in the alpine lakes of the Chinese Loess Plateau - Xiaosen Zhang; Huiru Han; Zhiping Zhang; Zhongwei Shen; Jingyue Zhang; Keming Ma; Jianbao Liu (Ecosphere, 2025)
Abstract Recent climate warming has resulted in the reduction of lake ice cover and significant changes in phytoplankton communities, but due to the traditional view of low production under lake ice in winter as well as the logistical challenges of winter conditions to field sampling, the influence of under‐ice limnological processes on winter diatom dynamics is rarely directly examined and thus remains unclear. Here, lake pelagic diatoms were monitored covering both the open‐water season and two ice‐covered winter seasons in three alpine lakes on the Chinese Loess Plateau to track diatom succession dynamics and assess the potential influences of under‐ice light and nutrient availability on diatom community. The results show clearly that diatom compositional changes during the open‐water season in all the lakes were simply linked with lake physical mixing/stratification regimes, while diatom community composition was not consistent between the two winter seasons in each lake under the combined influence of changing under‐ice nutrient and light conditions. In deep Lake Gonghai, total phosphorus (TP) explained equally the changes in winter diatom community with temperature, ice cover and associated light availability; in shallow Lake Pipahai, total nitrogen (TN) functioned as the major nutrient factor but was less important than light penetration through the ice; and in Lake Mayinghai, dissolved silica (DSi) outweighed the light effect of winter temperature and ice cover. Despite differing relative importance of nutrient factors between the different morphological types of lakes, winter diatom community changes in each lake were significantly linked with temperature, ice cover and associated changes in under‐ice light availability. This study provides a detailed picture that winter temperature and under‐ice limnological processes play a substantial role in diatom community dynamics in the alpine lakes of the Chinese Loess Plateau, and improves the understanding of limnological and ecological processes under ice and their driving mechanisms.